The Unorthodox Orbits of Substructure Halos - Ludlow, Aaron D; Navarro, Julio F; Springel, Volker; Jenkins, Adrian; Frenk, Carlos S; Helmi, Amina (The Astrophysical journal, 2009)
We use a suite of cosmological N-body simulations to study the properties of substructure halos (subhalos) in galaxy-sized cold dark matter halos. We extend prior work on the subject by considering the whole population of subhalos physically associated with the main system. These are defined as subhalos that have at some time in the past been within the virial radius of the halo's main progenitor and that have survived as self-bound entities to z = 0. We find that this population extends beyond three times the virial radius, and contains objects on extreme orbits, including a few with velocities approaching the nominal escape speed from the system. We trace the origin of these unorthodox orbits to the tidal dissociation of bound groups of subhalos, which results in the ejection of some subhalos along tidal streams. Ejected subhalos are primarily low-mass systems, leading to mass-dependent biases in their spatial distribution and kinematics: the lower the subhalo mass at accretion time, the less centrally concentrated and kinematically hotter their descendant population. The bias is strongest among the most massive subhalos, but disappears at the low-mass end: below a certain mass, subhalos behave just like test particles in the potential of the main halo. Overall, our findings imply that subhalos identified within the virial radius represent a rather incomplete census of the substructure physically related to a halo: only about one half of all associated subhalos are found today within the virial radius of a halo, and many relatively isolated halos may have actually been ejected in the past from more massive systems. These results may explain the age dependence of the clustering of low-mass halos reported recently by Gao et al., and has further implications for (1) the interpretation of the structural parameters and assembly histories of halos neighboring massive systems; (2) the existence of low-mass dynamical outliers, such as Leo I and And XII in the Local Group; and (3) the presence of evidence for evolutionary effects, such as tidal truncation or ram-pressure stripping, well outside the traditional virial boundary of a galaxy system.